Con quest! - Maggs, Sam (Imprint, 2020)
Twins Cat and Alex Gallo sneak away from their older sister at a GeekiCon convention in order to participate in a scavenger hunt called the Quest initiated by their favorite television actor. The pair will have to work together to complete the Quest, avoid their sister Fi, and elude an angry staffer who wants to kick them out for participating in the unsanctioned event.